Using GIS tools in the study of paleovalley in the Verchny Prut basin. Geoscience in the Carpathian and Black Sea Region - Костенюк, Людмила Володимирівна; Kosteniuk, Liudmyla (GCBS 2023 - Book of abstracts, 2023)
The use of new, modern methods of digital mapping and geoinformation tools in research allows us to take a fresh look at the seemingly already known and defined problematic issues of clarity of the stages of origin and formation of the basins of the river systems of the Ukrainian Carpathians and their gradual stabilization within the current boundaries. The long-standing and clearly defined position of leading specialists, Ukrainian geomorphologists (Andreychuk, 2012; Bayrak, 2008; Klapchuk, 1994) and hydrologists (Kostenyuk and Smyrnova, 2010), thanks to the use of new geographic information technologies and access to modern software, opens up new opportunities for its revision and clarification. An important aspect of studying basin systems in mountainous regions, such as the Ukrainian Carpathians, is the use of not just a cartographic research method with the corresponding results of visualization, zoning, or creation of appropriate mapping schemes, but also the use of system analysis. That is, thanks to GIS applications (TIN interpolation qgis), when creating appropriate models, we can reveal in more detail the complex issues of the reformation of ancient drainage valleys and their modern reflection in the relief of this territory. The complex and not fully disclosed issue of the reformation of ancient drainage valleys in the PliocenePleistocene period is extremely important for understanding modern channel processes in the rivers of the Upper Prut basin, as it still significantly affects the perception of the current pattern of the hydrosystem of the study basin and the inherited nature of channel macroforms in some of its sections.
Keywords: GIS; ГІС; басейн Верхнього Пруту; геоморфологія; палеодолини; SRTM; paleovalleys; Chornyy Cheremosh; Chorna Tysa; Lyuchka; Oslava